La politique internationale dans l’Arctique : une perspective américaine - Young, Oran (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1989)
The Arctic is emerging today as an international region whose importance in political, economic, and environmental terms rivals that of the world's other major regions. What remains in doubt, at this juncture, is how the Arctic states -not to mention others — will respond to this development in policy terms. Are these states likely to upgrade their capacity to handle Arctic issues by adding substantial Arctic expertise to their policy planning staffs; creating bureaux of Arctic or northern affairs in their foreign ministries; establishing effective interagency coordinating mechanisms to handle complex Arctic issues, or devising new Arctic policies to replace the policies of benign neglect they have long relied on in dealing with Arctic matters ? These are serious concerns whose resolution will take time and may differ from state to state. Just as the recognition of the Arctic as a distinctive international region has been a major development of the 1980s, the formulation of appropriate public responses to this development seems likely to become a central Arctic concern of the 1990s.